Microbial Profile During Pericoronitis and Microbiota Shift After Treatment - Huang, Xiuling; Zheng, Hui; An, Jingang; Chen, Shuo; Xiao, E; Zhang, Yi (Frontiers in Microbiology, 2020)
The microflora of the distal pocket is considered as the major cause of pericoronitis. How the oral microflora changes during pericoronitis and whether different types of impacted third molar harbor the same microflora are still unknown. Saliva, subgingival plaque and gingival plaque of mandibular third molars (M3Ms) were collected from twelve patients with acute pericoronitis. They were given local irrigation or local irrigation + antibiotics according to symptoms. Samples were harvested at the first visit with pericoronitis, 1 week after treatment, and 6 weeks after treatment. 16S rRNA gene PCR products were generated and sequenced after DNA isolation. Comparison of three sampling sites showed that, the subgingival plaque of M3Ms had most remarkable changes in symptomatic period, including a significant increase in microbial richness and a convergent trend in microbial composition. In pericoronitis, horizontal and vertical impacted M3Ms harbored distinct microbiome both in gingival and subgingival plaque. After treatment, the subgingival microbiome was altered and largely returned to the state in asymptomatic period. Furthermore, the post-treatment microbiome shift in the combined treatment group (local irrigation + antibiotics) was greater than that in the local treatment group. In summary, the distal subgingival microbiota of M3M was most likely to be associated with the pathogenesis of pericoronitis. The post-treatment microbiota shift of M3M proved the effectiveness of treatment. The inclination type of impacted M3Ms and treatment method would make a difference to the pericoronal microbiota.